Micromorphology and microchemistry of selected Cryosols from maritime Antarctica - Schaefer, Carlos Ernesto G.R.; Simas, Felipe N.B.; Gilkes, Robert J.; Mathison, Charter; Costa, Liovando M. da; Albuquerque, Miriam A. (Geoderma, 2008)
Little information is available on the microstructure of Cryosols from maritime Antarctica, and the present study characterizes the main soil types commonly found in ice-free areas of Admiralty Bay, King George Island. Four pedons were selected for micromorphological and microprobe analysis. The type of microstructure observed in the soils is strongly influenced by the lithological composition and arrangement, with a high proportion of primary minerals in all particle fractions. The oxidation of sulphides is the most important pedogenetic process in acid sulphate soils from maritime Antarctica and results in intense chemical weathering of minerals and formation of Na-jarosite, amorphous Fe-oxides and kaolinite. Jarosite forms illuvial coating within cryodesiccation fractures and is associated with large amounts of amorphous Fe minerals that possess a high P adsorption capacity. In ornithogenic soils, the phosphatization process enhances soil acidity and chemical alteration of the substrate and is the main soil-forming process in ornithogenic soils. P-rich solutions penetrate cryodesiccation fractures and cleavage planes in large clasts and preferentially react with volcanic glass. Soil reaction with P-rich leachates leads to the progressive displacement of Si from rock minerals, coupled with reacting of P with Al, Fe, K and Mg to form various amorphous and crystalline P forms. Cryoclastic weathering and cryoturbation result in high levels of fine P-rich aggregates down the profile. Chemical weathering is more pronounced in maritime Antarctica than previously thought, especially for acid sulphate and ornithogenic soils. The utilization of micromorphological and microchemical techniques proved to be extremely useful for a better understanding of pedogenesis in these poorly known Antarctic soils.
Keywords: Ornithogenic soils; Antarctic soils; Cryoturbation; Gelisols